Can there be a wave-like association between economic growth and inequality? Theory and lessons for East Asia from the Middle East - Partha Gangopadhyay; Biswa N. Bhattacharyay (Center for Economic Studies and ifo Institute (CESifo), 2012)
High income growth in many countries in East Asia and the Middle East has been accompanied by increasing income inequality and widening gaps between rich and poor, and urban and rural. It is therefore it is important to examine the interrelationships between inequality and economic growth. This paper develops a simple model to establish that the change in income growth rate is a non-linear function of the income growth if policy makers try to influence economic growth. As a result, inequality and growth bear a non-linear relationship: for low values of inequality, economic growth rate is an inverted U-shaped of inequality. This function becomes U-shaped for values of inequality beyond a critical value of inequality. As a result, the relationship between growth and inequality can take the form of a wave. This simple theoretical model is a sufficient case to explain why previous empirical studies might have failed to reach a consensus between economic growth and inequality. The paper estimates the model empirically by using a set of panel data for ten Middle Eastern countries. The empirical analysis finds statistical support for a possible wave like relationship between growth and inequality, which can bear ominous messages for using equitable growth in fighting poverty. Rapid growing developing economies need to adopt appropriate policies for achieving an optimal mix of inequality and growth. Promoting inclusive growth together with good governance is crucial to ensure more equity and social stability.
Keywords: H21; O11; O15; O41; 330; growth; inequality; poverty; East Asia and the Middle East; Wirtschaftswachstum; Einkommensverteilung; Soziale Ungleichheit; Armut; Mittlerer Osten; Ostasien